In situ measurements of temperatures in Kuala Lumpur area - Ibrahim, Illyani; Abu Samah, Azizan; Fauzi, Rosmadi; Jaafar, Samsuddin (2015)
The current situation of environmental condition becomes an importance niche that is crucial to be understand by many researchers. This research attempts carried out an investigation on the temperature daytime measurement across different land cover areas. These land cover types were selected for interrogating the temperature varies in different measurement that was conducted. The method used in this study by utilizing vehicle equipped with a surface and air temperature sensor and a global positioning system (GPS) receiver, and measuring temperature to the same location in a different day period. The finding of this study is the playing field shows a hot pocket of temperature compared to the other areas, including residential, roads and commercial. Another finding is a consistency of the heat island areas was found; Sungei Wang Plaza and Dataran Merdeka of POI (Point of Interest) as the main attraction area of people and tourists. This study leads to the propose for the land use map in the urban planning department not to include playing fields and golf course under green areas, as it does not cool down the temperatures.